The PERCEPTION OF NON-ENGLISH EDUCATION STUDY PROGRAM STUDENTS ON INSTITUTIONAL TOEFL TEST - Meisuri Meisuri; M. Ridho Kholid; Agus Hidayat (Jurnal Scientia, 2022)
Universities and other institutions of higher learning frequently require students to complete an English proficiency test before moving on to the next phase of education. Despite the fact that there are a variety of TOEFL tests, the institution is most likely to use an institutional TOEFL test. The same thing happens at the Raden Intan State Islamic University in Lampung, where students must get a minimum TOEFL score to take the thesis examination or graduate. Students from all study programs must acquire a minimum score of 400 on the TOEFL test to be deemed fluent in English. Students' opinions on the usage of the institutional TOEFL as a measure of English competence were examined in this study. Non-English Education study program students were the focus of this study, which surveyed their perceptions on utilizing the institutional TOEFL test. The researchers surveyed 90 students who had taken the TOEFL test at the Language Development Center of UIN Raden Intan Lampung. The researchers sent out a questionnaire to collect data. The questionnaire includes five statements to provide a picture of students' perceptions of the TOEFL test. Based on the analysis, the researchers found that many respondents claimed TOEFL could measure English proficiency. Also, they found the test is effective. Most respondents disagree that the institutional TOEFL test measures four basic English skills. They thought the test could not measure the four English skills because it lacked writing and speaking aspects. Most respondents disagree with using the institutional TOEFL as the only English proficiency test since it is too difficult for those who don't use English daily. They thought there must be other English proficiency tests that could be utilized Keywords: